Aging mitochondria in the context of SARS-CoV-2: exploring interactions and implications - Delpino, M. Victoria; Quarleri, Jorge (Frontiers in Aging, 2024)
The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has presented global challenges with a diverse clinical spectrum, including severe respiratory complications and systemic effects. This review explores the intricate relationship between mitochondrial dysfunction, aging, and obesity in COVID-19. Mitochondria are vital for cellular energy provision and resilience against age-related macromolecule damage accumulation. They manage energy allocation in cells, activating adaptive responses and stress signals such as redox imbalance and innate immunity activation. As organisms age, mitochondrial function diminishes. Aging and obesity, linked to mitochondrial dysfunction, compromise the antiviral response, affecting the release of interferons, and worsening COVID-19 severity. Furthermore, the development of post-acute sequelae of SARS-CoV-2 infection (PASC), also known as long COVID has been associated with altered energy metabolism, and chronic immune dysregulation derived from mitochondrial dysfunction. Understanding the interplay between mitochondria, aging, obesity, and viral infections provides insights into COVID-19 pathogenesis. Targeting mitochondrial health may offer potential therapeutic strategies to mitigate severe outcomes and address long-term consequences in infected individuals.